"Dance Saved My Life": Kadir Memiş's Life Story and the (Re)Framing of Identity through Dance. Issue 1 (2nd January 2020) - Kurt, Berna
Abstract: A Turkish artist living in Germany, Kadir "Amigo" Memiş is known for choreographies that combine street dance or breaking with traditional dances of Turkey. His story in Germany began with social integration problems and the trauma of losing his brother, but it continued with his adaptation to the diaspora through the medium of dance. Using thematic analysis to construct a life story based on Memiş's self-narratives, I aim to demonstrate how the artist's engagement with hip-hop culture in the diaspora helped him overcome his troubles and construct a new, artist's identity.